ASSESSMENT OF IMMUNIZATION COVERAGE AND FACTORS THAT DETERMINE DROPOUT RATE AMONG CHILDREN 0- 23 MONTHS OF AGE, IN ESAN CENTRAL LGA, EDO STATE, NIGERIA (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Vaccination is a crucial preventive measure, averting an estimated 2.5 million deaths among children under the age of five. Despite global efforts, including the immunization of approximately 116 million infants in 2018, comprising 86% of the population, vaccine-preventable diseases continue to claim over 1.5 million lives annually. This study focused on evaluating immunization coverage and identifying factors contributing to dropout rates in selected Healthcare Centers within the Esan Central Local Government Area of Irrua, Edo State.A cross-sectional study design was employed, with 415 respondents purposively selected. Data were collected through self-administered questionnaires and analyzed using descriptive and inferential statistics. The findings revealed that the majority of respondents were aged 25-34 years (44.25%), predominantly female (94.13%), married (56.48%), and had at least attained a secondary level of education (48.6%). Furthermore, a significant portion reported being housewives (31.05%) or engaged in business (26.60%). The majority identified as Christians (69.78%), while 31.05% practiced Islam. Regarding ethnicity, 78.24% were from the Esan tribe, while Ibos and Hausas represented 2.93% each, and other ethnicities accounted for 12.71%.Bivariate analysis indicated associations between immunization dropout and various factors, including the child's health status during scheduled appointments (X2=10.0122, df=1, p=0.001), maternal awareness of immunization schedules (X2=29.13765, df=1, p=0.05), place of delivery (X2=78.5586, df=1, p=0.01), fear of side effects (X2=29.0515, df=1, p=0.05), poor knowledge of appointment dates (X2=18.1445, df=1, p=0.01), and financial constraints (X2=49.1877, df=1, p=0.01).Chi-square tests revealed a level of association with a p-value >0.05, leading to the acceptance of the null hypothesis. The study concluded that immunization coverage remains suboptimal among children aged 0-23 months. Recommendations include addressing factors influencing immunization coverage to mitigate dropout rates and enhance overall immunization coverage.